Peningkatan Pencapaian Kualitas Lulusan D3 Teknik Elektro dengan Model Teaching Factory - Elsanda Merita Indrawati (Jurnal Penjaminan Mutu, 2017)
The purpose of this study, namely: (1) determine systematically the implementation of teaching factory model of the learning process D3 electrical engineering; (2) determine the achievement quality D3 graduate in electrical engineering and Teaching Factory models. The approach used is a qualitative approach, data collection techniques through observation, interviews, documentation. Results of the assessment showed that the implementation of teaching factory model of the learning process D3 Electrical Engineering done quite well, starting from the standard of competence, media, lecturers, students, use and maintenance, production, marketing, evaluation has been structured well enough. But there are still shortcomings in the establishment of management due to the formation of management, the management structure remains unclear resulted in the implementation of the model is less than the maximum teaching factory in the Department of Electrical Engineering D3. Implementation of teaching factory in D3 Electrical Engineering UN PGRI Kediri has been going pretty well, the resulting product has a quality worth selling, economical and multifunctional, the students are expected after graduation in addition to be absorbed in the industrialized world are working as interpreneur and employers on the products they produce so with the application of teaching factory, the quality D3 Electrical Engineering increasing